The Paradox of Legibility: Domestic Violence and Institutional Survivorhood. (29th May 2018) - Sweet, Paige L
Abstract: Existing literature has demonstrated that victims of domestic violence and rape undergo processes of discipline when they interact with legal structures, transforming themselves into "worthy victims." Intervening in this literature, I show how the medicalization of institutions surrounding domestic violence creates conditions under which women must prove their survivorhood, performing psychological recovery to achieve institutional legibility. Legal and therapeutic institutions create a matrix of demands on women's lives, shaping their practices of survival and performances of self. Through interviews with domestic violence survivors, I show that women engage three strategies of transformation to make themselves credible survivors: (1) extracting domestic violence from their life stories; (2) explaining abuse through "self-esteem;" (3) performing survivorhood through "respectable" motherhood and sexuality. Through these processes, women craft a domestic violence narrative and an institutional performance of survivorhood, both of which allow them to navigate institutional pressures. These therapeutic narratives and performances, however, also rewrite the structural elements of violence into (feminized) accounts of psychological failure and overcoming. Thus, women navigate a paradox when they become survivors: they must tell stories of psychological recovery, even as those stories obfuscate the very infrastructure of violence. It is this disjuncture between individualized narratives of harm and the structural work of survival that I examine in this work. I develop the concept of the "paradox of legibility" to generalize this disjuncture, and to highlight women's labor of making themselves credible amidst structural and institutional constraints.